Celebrating Moore works from the collection of the Henry Moore Foundation - Moore, Henry 1898-1986 (Lund Humphries, 2006)
"Celebrating Moore is the biggest and most comprehensive single volume to be produced on the artist's oeuvre, and reproduces in colour over 250 of Henry Moore's most important sculptural works." "The core of the book consists of a selection of 278 works from the Henry Moore Foundation Collection, illustrated in colour and with full catalogue information. Extended captions have been contributed by a range of distinguished artists, art critics and art historians - those who knew Moore or have previously written about him." --Book jacket.